Reading the near-death experience from an African perspective - Agai, Jock (HTS teologiese studies, 2015)
The scientific study of near-death experience (NDE) teaches that NDE does not entail evidence for life after death, but a study of NDE from an African perspective implies that NDE could serve as a yardstick which supports African traditional beliefs concerning death and resurrection. Using references from Ancient-Egyptian afterlife beliefs and those of the Yorubas of Nigeria, I argue that, for Africans, the percipients of NDE did not only come close to death but are regarded as having truly died. The purpose of this research is to initiate an African debate on the subject and to provide background-knowledge about NDE in Africa for counsellors who counsel NDE percipients that are Africans.